The Effect of a Selected Motor Program on Manipulative Skills in 4-6-Year-Old Boys - Kayvan Norouzi; Hassan Khalaji; Mahmodd Sheikh; Hakimeh Akbari (University of Tehran, 2011)
The purpose of this study was to investigate the effect of a selected motor program (as a motor experience) on manipulative skills in 4-6-year-old boys. 40 subjects were selected randomly using a personal information questionnaire. After the pretest, the Ulrich's test of Gross Motor Development (2000) including fundamental motor skills, locomotors skills, manipulative skills and controlling instruments was used and the subjects were randomly divided into two groups of selected motor program (age: 58.9 months, SD: 8.57); one of these groups experienced the activities of researcher's selected motor program 24 sessions, 30 minutes per session while the other group (control) enjoyed their casual activities. After 24 sessions, two groups participated in the posttest. To test the hypotheses, Kolmogorov-Smirnov and independent and dependent t student tests were used. The results showed that a selected motor program had more effects on the development of manipulative skills when compared with casual activities (P